Technology-based learning interventions on mathematical problem-solving: a meta-analysis of research in Indonesia - Himmatul Ulya; Sugiman Sugiman; Raden Rosnawati; Heri Retnawati (Institute of Advanced Engineering and Science, 2024)
Mathematical problem-solving is important for learning mathematics and is needed in the 21st century. In the 21st century, education technology has been complementing every learning activity. Research on learners’ mathematical problem-solving improvement increased rapidly over the last few decades. This study examined the effectiveness of technology-based mathematics learning interventions on learners’ mathematical problem-solving at all levels of education in Indonesia. The researchers only took meta-analysis research from 2015 to 2023 from indexing databases, such as Scopus, Web of Science, Google Scholar, and Science and Technology Index (SINTA) indexers. The collected research articles were from only national journals in Indonesia. The screened data became the research results, containing the mean, standard deviation, number of samples (N), and the scale used in the research. This research had 19 independent studies in this meta-analysis. The data analysis applied meta-analysis, specifically the mean effect size value. The results of data analysis using Jeffrey’s Amazing Statistics Program (JASP) software showed the effective implementation of innovative and fun technology-based mathematics learning interventions. These findings highlighted the importance of incorporating technology into mathematics education and its potential for improving learners’ problem-solving skills.